2014
DOI: 10.1007/s11121-014-0522-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Patterns of Postpartum Alcohol Consumption by Age: A Longitudinal Analysis of Adult Urban Mothers

Abstract: The purpose of this study is to investigate a) longitudinal patterns of maternal postpartum alcohol use as well as its variation by maternal age at child birth; b) within maternal age groups, the association between other maternal characteristics and alcohol use patterns for the purposes of informed prevention design. Study sample consists of 3,397 mothers from the Fragile Families and Child Wellbeing Study representing medium and large U.S. urban areas. Maternal drinking and binge drinking were measured at ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Further informing clinical screening of recent mothers for risk of domestic violence, the descriptive findings from this study are consistent with the profile of higher risk drinking identified in other studies — that higher risk drinkers are more likely to be White (Little, Lambert, & Worthington-Roberts, 1990), unmarried (Jagodzinski & Fleming, 2007), to have at least a college education (Williams Brown, Carmichael Olson, & Croninger, 2010), to report a higher household income (R. Caetano, Ramisetty-Mikler, Floyd, & McGrath, 2006), and to give birth in their mid-30s or older (Liu et al, 2015). We also found that higher risk drinkers are less likely to have additional children in the home.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further informing clinical screening of recent mothers for risk of domestic violence, the descriptive findings from this study are consistent with the profile of higher risk drinking identified in other studies — that higher risk drinkers are more likely to be White (Little, Lambert, & Worthington-Roberts, 1990), unmarried (Jagodzinski & Fleming, 2007), to have at least a college education (Williams Brown, Carmichael Olson, & Croninger, 2010), to report a higher household income (R. Caetano, Ramisetty-Mikler, Floyd, & McGrath, 2006), and to give birth in their mid-30s or older (Liu et al, 2015). We also found that higher risk drinkers are less likely to have additional children in the home.…”
Section: Discussionsupporting
confidence: 89%
“…This is a critical question because women’s consumption of alcohol tends to resume post childbirth (Liu, Mumford, & Petras, 2015; Substance Abuse and Mental Health Services Administration, 2008). Moreover, while research indicates that maternal alcohol use and domestic violence are likely confounded by partner alcohol use, most studies do not take into account partner alcohol use (Jester et al, 2000; Martin et al, 2003; Meschke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a concerning level of concurrent use during the perinatal period and shared risk factors, e.g., mental disorders (Ingersoll, Hettema, Cropsey, & Jackson, 2011), being unmarried (Tsai, et al, 2010), curtailed breastfeeding (Jagodzinski & Fleming 2007), longitudinal patterns of maternal smoking (Mumford & Liu 2015) and drinking (Liu, Mumford, & Petras, 2015) have only been modeled separately. To inform public health and clinical efforts in better allocating prevention efforts, we investigate distinct trajectories representing single and dual usage of alcohol and cigarettes by mothers from pre-conception through the early parenting years, and the extent to which mothers’ baseline characteristics are associated with these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Little et al (2009) investigate trajectories of alcohol use from early adolescence to age thirty as a function of parenthood timing, finding that adolescent parenthood is linked to faster increases during adolescence, and higher sustained levels of, in the volume of alcohol consumption. Finally, a pair of studies by Liu, Mumford & Petras (2015 use growth mixture models to examine heterogeneous trajectories of mothers' alcohol use up to five years after (and immediately before) birth.…”
Section: Alcohol Usementioning
confidence: 99%
“…In sum, the (small) body of evidence regarding a potential moderating effect of fertility timing on trajectories of alcohol use is inconsistent -some research (Wolfe 2009;Little et al 2009) finds that early birth timing is linked to faster subsequent increases in alcohol use, while others (Liu, Mumford & Petras 2015; show the opposite effect.…”
Section: Alcohol Usementioning
confidence: 99%